Modern Native Library and Information Standards: Terminological Analysis - Strishenets Nadiia (Bìblìotečnij vìsnik, 2018)

(untitled)
The article examines the quality of the modern Ukrainian library and information standards in terminology. The main problems of it are highlighted and ways of their solution are indicated by the author. Over the recent years, some standards in library and information terminology have been produced in Ukraine. The analysis demonstrates that the terminology of these standards partly needs to be improved. Library and information science (LIS) terminology has been developing rapidly. Since the standards were prepared by not the specialists in LIS its terminology is outdated sometimes. Outside the standards there is a group of new terms and concepts from the international cataloging standard «Resource Description and Access», IFLA Functional Requirements for Bibliographic Records, Functional Requirements for Authority Data and for Subject Authority Data, etc. As the standards address a fundamental requirement for effective communication the definition of terms needs improvement. All concepts have to be represented in an unambiguous manner. The findings suggest that a special problem is the terminological equivalents in foreign languages for LIS terms. Equivalents in French, for example, are presented only occasionally in some standards. The author concluded that within the framework of the Association Agreement between Ukraine and the European Union it is also very important to harmonize national standards with international ones and organize their translation into Ukrainian language.